Novel Design for Direct Torque Control System of PMSM - HUANG Xu-chao; LIN Rong-wen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Nowadays, with the rapid development of high-performance servo system, The conventional permanent magnet synchronous motor (PMSM) Direct Torque Control (DTC) system has large torque ripple in low speed which cannot be well adapted to today`s development. The main reason is because the number of voltage vectors provided by the two-level inverter is only six and the relationship between voltage vector and torque is not clear[1-5.10-12]. In this paper, the basic concept of direct torque control of permanent magnet synchronous motor is investigated in order to emphasize the effects produced by a given voltage vector on stator and torque variations in this paper. Modified the voltage sector switching table, a novel DTC scheme for the permanent magnet synchronous motor is proposed which is using a novel three-level inverter. An improvement of the drive performance can be obtained by using the novel DTC scheme. The simulation results showed that the scheme could reduce the torque ripple in low speed and improved the stability of the motor under the condition of keeping the system dynamic performance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2391